Boosting the charge transfer of FeOOH/Ni(OH)2 for excellent oxygen evolution reaction via Cr modification. Issue 28 (25th June 2021) - He, Yan; Yu, Tao; Wen, Hui; Guo, Rui
Abstract : Cr-Doped FeOOH/Ni(OH)2 electrocatalysts were prepared via a facile hydrothermal method at 120 °C. The electrocatalyst exhibited outstanding OER performance, with an overpotential of 291 mV at 50 mA cm −2 . Abstract : For the electrocatalytic oxygen evolution reaction (OER) in alkaline media, there is an urgent need to optimize the adsorption strength of OH*. Here, a flower-like hybrid of Cr-doped FeOOH/Ni(OH)2 was used as an OER catalyst with a low overpotential of 291 mV at 50 mA cm −2 . The results showed that faster charge transfer was achieved at the electrode/solution interface during the OER process after the FeOOH/Ni(OH)2 was modified by Cr, which facilitates the rate-determining step of the Volmer reaction. Furthermore, the results of faradaic efficiency and X-ray photoelectron spectroscopy (XPS) measurements confirmed that the synergistic effect between the ternary metal and oxygen vacancies led to excellent OER performance. This work provides a new strategy for the preparation of high-efficiency and low-cost oxygen evolution electrocatalysts.